Hydraulic conductivity of Molisolls irrigated with sodic-bicarbonated waters in Santa Fe (Argentine) - Ghiberto, Pablo Javier (2007)
Irrigation waters with high sodicity and low salinity levels may deteriorate soil physical properties, consequently affecting the water movement in the soil. The objectives of this study were: (i) to evaluate the effect of supplemental irrigation with waters that have a residual sodium carbonate (RSC) [Richards, L.A. (Ed.), 1954. Diagnóstico y rehabilitación de suelos salinos y sódicos. Manual de Agricultura, vol. 60. Limusa, México] greater than 1.25 mmolc L-1 on the hydraulic conductivity (K) of Hapludolls and Argiudolls located in Santa Fe State (Argentina) and (ii) to identify the possible causes of K alteration. Irrigated and non-irrigated plots were selected to evaluate soil bulk density, water dispersed clay content, and K in two depth intervals: 0-7 and 15-25 cm. K was measured with tension infiltrometers at three tension values: 0, 0.15, and 0.3 kPa. Increases in ESP in both depths from 1 to 10 caused a 10% to 79% decrease in K in the irrigated relative to non-irrigated treatments. Changes in K were associated with increased clay dispersion suggesting that this factor results in failure of the structure, resulting in increased blockage of soil pores. Between 51% and 62% of the total clay was dispersed in water in irrigated treatments, and 36-44% in non-irrigated treatments. Results emphasize the importance of preventing soil dispersion. This process induces degradation of big pores, especially those with equivalent radii greater than 1000 μm, which is essential for quick water flow. The conductivity of these pores was decreased from 48% to 79% in irrigated relative to non-irrigated treatment. A field method is proposed to determine when reclamation practices should begin.